Fatty Acid Synthase expression promotes the malignant features of cholangiocarcinoma cells and predicts shorter survival in patients. (March 2023) - Lori, G.; Raggi, C.; Piombanti, B.; Pastore, M.; Booijink, R.; Navari, N.; Rovida, E.; Gastaldelli, A.; Andersen, J.; Lewinska, M.; Marra, F.
Abstract : Background and Aims: Cancer cells are exposed to a metabolically challenging environment with scarce availability of nutrients, and alterations in lipid metabolism may affect the cellular response to drugs. We hypothesize that fatty acids (FA) modulate the biology of cholangiocarcinoma (CCA) cells and the development of stemness features. Method: CCA cells (HuCCT-1 or CCLP1) were treated with monounsaturated FAs (132μM oleic or 100μM palmitoleic acid). Self-renewal ability was tested with a colony formation assay. Cancer stem cell- (CSC)-enriched spheres were obtained growing cells in anchorage-independent conditions and selective medium. Five-year overall survival (OS) was analyzed in 34 patients with CCA sub-grouped based on fatty acid synthase (FASN) expression. Desaturation index and triglyceride de novo synthesis were performed by lipidomic analysis. NSG mice were injected with CCLP1 spheres and treated with the FASN inhibitor orlistat (240mg/Kg). Tumor volume was measured with Vevo LAZR-X imaging station. RTPCR array on tumor masses was performed using the QuantiNova LNA PCR Panel. Results: Exposure of CCA cell lines to FAs increased cell proliferation and activated growth and survival pathways, including AKT and ERK1/2. Exposure to FA made CCA cells less sensitive to the toxic effects of chemotherapeutic agents, and modulated the expression of ABC transporters involved in drug resistance. The colony forming ability of CCA cells was increased by FAs, and was associated with upregulation of genes controlling epithelial-mesenchymal transition and stemness. Expression levels of genes involved in lipid metabolism were upregulated in CSC-enriched spheres as well as the percentage of desaturated TGs. FASN inhibition by orlistat decreased cell proliferation and CSC or EMT markers. In a xenograft model of CCA, tumor volume was significantly lower in mice treated with orlistat. Accordingly, expression of genes involved in cell proliferation was downregulated while the one of tumor suppressor genes increased. In a series of CCA patients, the expression of FASN correlated with OS. Conclusion: FA promote malignant features of CCA and increase CSC markers. FASN expression levels correlate with survival in patients with CCA and promote CCA growth in mice. Lipid metabolism could be a new target to block CCA progression.